2010
DOI: 10.1016/j.bpj.2009.12.4272
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Glu-166 Blocks the Substrate-Induced Dimerization of SARS Coronavirus Main Protease

Abstract: The maturation of SARS coronavirus involves the autocleavage of polyproteins 1a and 1ab by the main protease (Mpro) and a papain-like protease; these represent attractive targets for the development of anti-SARS drugs. The functional unit of Mpro is a homodimer, and each subunit has a His-41cdots, three dots, centeredCys-145 catalytic dyad. Current thinking in this area is that Mpro dimerization is essential for catalysis, although the influence of the substrate binding on the dimer formation has never been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
153
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(175 citation statements)
references
References 36 publications
19
153
0
Order By: Relevance
“…Based on the c(s) distribution analysis, we observe that there are quaternary structural changes at various substrate concentrations (Fig. A broad peak located between the monomeric and dimeric Mpro was detected at a substrate concentration of 50 lM, which suggest that Mpro is a rapidly self-associating protein [16]. This is consistent with our recent observations during routine SV experiments, which have shown that the presence of substrate can induce a quaternary structural change in Mpro [16].…”
Section: Data Interpretationsupporting
confidence: 89%
See 3 more Smart Citations
“…Based on the c(s) distribution analysis, we observe that there are quaternary structural changes at various substrate concentrations (Fig. A broad peak located between the monomeric and dimeric Mpro was detected at a substrate concentration of 50 lM, which suggest that Mpro is a rapidly self-associating protein [16]. This is consistent with our recent observations during routine SV experiments, which have shown that the presence of substrate can induce a quaternary structural change in Mpro [16].…”
Section: Data Interpretationsupporting
confidence: 89%
“…At that time, the complicated data analysis problems impeded the wide spread use of this technique [9]. All the results from the AUC support the existence of substrate-induced dimerization of Mpro, which is consistent with our other studies [16]. This has changed because advances in software have made handling huge datasets only a few keyboard strokes away [3,4,13,14].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…The AUC experiments were performed on a XL-A analytical ultracentrifuge (Beckman, Fullerton, CA) using an An-50 Ti rotor [15,[17][18][19][20]. The sedimentation velocity experiments were performed using a double-sector epon charcoal-filled centerpiece at 20°C with a rotor speed of 42,000 rpm.…”
Section: Analytical Ultracentrifugation Analysismentioning
confidence: 99%